The absolute configuration of 1-(3 ',4 '-dihydroxycinnamoyl)cyclopentane-2,3-diol from the Amazonian tree Chimarrhis turbinata - Cardoso, Carmen Lucia; Bolzani, Vanderlan da Silva [UNESP]; Siqueira Silva, Dulce Helena; Ishii, Hideki; Berova, Nina; Nakanishi, Koji (Amer Chemical Soc, 2006)
An antioxidant, 1-(3',4'-dihydroxycinnamoyl) cyclopentane-2,3-diol [ or ( E)-2,3-dihydroxycyclopentyl-3-(3',4'-dihydroxyphenyl) acrylate ( 1)], and two known trans- and cis-chlorogenic acid methyl esters were isolated from the ethanolic extract of the leaves of Chimarrhis turbinata. The relative configuration of 1 was determined by NMR and by comparison of the circular dichroic spectrum ( CD) with those of the enantiomers of synthetic 3', 4'-dimethoxycinnamoyl analogues. The absolute configuration of one of the synthetic enantiomers was determined using the CD exciton chirality method. This established the structure of naturally occurring 1 as (E)- 2,3-dihydroxycyclopentyl- 3-(3', 4'-dihydroxyphenyl) acrylate.